JOHANNESBURG’S WATER TARIFF STRUCTURE - KRYSTALL, NATHAN (My University, 2011)
This research report contains a critical examination of Johannesburg‘s water tariff structure. The examination employs normative criteria formulated through reviews of tariffs in theory and in practice, and of the political economy of water supply in Johannesburg. The research found that the tariff structure is generally progressive, geared towards furthering the social objectives of ensuring the universal provision of an accessible, affordable, and sufficient supply of safe water. At the same time, the research found that there are shortcomings within the tariff structure and social, economic, and political factors that threaten to undermine the extent to which these objectives can be achieved. The report‘s analysis includes recommendations that could enable the tariff structure to better serve as a central mechanism in meeting the objectives of sustainable and equitable water supply.
MBA thesis - WBS
Keywords: Water supply; Johannesburg Water